SUBJECT OF A PROCEDURAL SETTLEMENT SUBJECT (ITS TERMS) IN CIVIL PROCEDURE LAW OF THE REPUBLIC OF LATVIA - Sintija Finka (European Scientific Journal, ESJ, 2014)
The present article analyzes a subject of a settlement in civil procedural law, inspecting judicial regulation of a procedural settlement (further in the text − settlement) in the Republic of Latvia in connection with a statutory regulation of other countries, jurisprudence, and judicature. The aim of this article is to analyze a subject (its terms) of settlement, bringing into light basic features of a settlement and its legal character.